ANALYSIS OF READING LITERACY IN PHYSICAL BOOKS AND E-BOOKS AMONG 6TH SEMESTER PGSD STUDENTS - Diina Septi Sevia (Teaching and General Education Studies, 2025)
This study aims to analyse the reading literacy level of 6TH semester PGSD students toward two types of reading media, namely physical books and e-books. The background of this study is based on changes in students' reading patterns due to technological advances that have made it easier to access information through digital media. The research method used is descriptive qualitative with a case study approach. The research subjects consisted of 30 active sixth-semester students selected through purposive sampling. Data were collected via an online questionnaire and analysed thematically. The results showed that 80% of students preferred e-books due to their practicality, efficiency, and flexibility in access. Among them, 45% were in the high literacy category, 37.5% in the moderate category, and 17.5% in the low category. Most students read to complete academic assignments, not out of personal interest. Reading barriers include technical, physical, and psychological factors. These findings highlight the importance of learning strategies that not only leverage technology but also promote the enhancement of interest and literacy skills comprehensively.